Reactive Postural Responses After Mild Traumatic Brain Injury and Their Association With Musculoskeletal Injury Risk in Collegiate Athletes: A Study Protocol - Morris, Amanda; Cassidy, Benjamin; Pelo, Ryan; Fino, Nora F.; Presson, Angela P.; Cushman, Daniel M.; Monson, Nicholas E.; Dibble, Leland E.; Fino, Peter C. (Frontiers in Sports and Active Living, 2020)
Background: Deficits in neuromuscular control are widely reported after mild traumatic brain injury (mTBI). These deficits are speculated to contribute to the increased rate of musculoskeletal injuries after mTBI. However, a concrete mechanistic connection between post-mTBI deficits and musculoskeletal injuries has yet to be established. While impairments in some domains of balance control have been linked to musculoskeletal injuries, reactive balance control has received little attention in the mTBI literature, despite the inherent demand of balance recovery in athletics. Our central hypothesis is that the high rate of musculoskeletal injuries after mTBI is in part due to impaired reactive balance control necessary for balance recovery. The purpose of this study is to (1) characterize reactive postural responses to recover balance in athletes with recent mTBI compared to healthy control subjects, (2) determine the extent to which reactive postural responses remain impaired in athletes with recent mTBI who have been cleared to return to play, and (3) determine the relationship between reactive postural responses and acute lower extremity musculoskeletal injuries in a general sample of healthy collegiate athletes. Methods: This two-phase study will take place at the University of Utah in coordination with the University of Utah Athletics Department. Phase 1 will evaluate student-athletes who have sustained mTBI and teammate-matched controls who meet all the inclusion criteria. The participants will be assessed at multiple time points along the return-to-play progress of the athlete with mTBI. The primary outcome will be measures of reactive postural response derived from wearable sensors during the Push and Release (P&R) test. In phase 2, student-athletes will undergo a baseline assessment of postural responses. Acute lower extremity musculoskeletal injuries for each participant will be prospectively tracked for 1 year from the date of first team activity. The primary outcomes will be the measures of reactive postural responses and the time from first team activity to lower extremity injury. Discussion: Results from this study will further our understanding of changes in balance control, across all domains, after mTBI and identify the extent to which postural responses can be used to assess injury risk in collegiate athletes.